Changes in nitric oxide levels and erythrocyte arginase activities in patient with Down syndrome - Ozbey, Ulku; Seyran, Ayse; Erisir, Mine; Benzer, Fulya; Savucu, Yuksel (Academic Journals, 2012)
Down syndrome is a chromosome abnormality with specific clinical symptoms and mental retardation caused by trisomy of chromosome 21. There is evidence that oxygen free radicals play an important role in the pathophysiology of many neuropsychiatric disorders. Although, it has not been investigated yet, several recent studies proposed that nitric oxide related to oxidative stress and arginase may have a pathophysiological role in mental retardation. The purpose of this study was to determine plasma nitric oxide levels and erythrocyte arginase activities in patients with Down syndrome and in healthy children. Plasma nitric oxide levels and erythrocyte arginase activity were measured in 20 patients with Down syndrome (median age: 15.6 +/- 7.5) and 20 age-matched healthy subjects (median age: 16.2 +/- 7.4). Significant differences were found between erythrocyte arginase activity of the patients with Down syndrome (35.2 +/- 2.7 U/g hemoglobin (Hb)) and those of healthy children (43.5 +/- 2.9 U/g Hb), (P < 0.05). But we have not found any statistical difference between persons with Down syndrome and control group for nitric oxide (P > 0.05). It was concluded that the level of erythrocyte arginase activity could be considered as a useful marker for assessing the level of mental retardation in children with Down syndrome.
Keywords: Down syndrome; erythrocyte arginase; nitric oxide; mental retardation; oxidative stress